Building of an arrest houses network ensuring execution of punishment - Korneev Sergey; Prys Evgeniy; Mityukova Yuliya; Bystrova Yuliya (BIO Web of Conferences, 2023)
Since the adoption of the current Criminal Code of Russian Federation, arrest as a type of criminal punishment has not been reflected in law enforcement activities due to the lack of specialized state institutions on the territory of Russian Federation - arrest houses. The authors believe that this fact narrows the variability of the means of criminal legal influence of the state in the fight against crime and does not reveal the true potential of arrest. According to preliminary calculations, the number of those sentenced to arrest in Russian Federation may be approximately 60-70 thousand people a year. To accommodate them, it is necessary to build at least 140 arrest houses in the constituent entities of Russian Federation. The construction and maintenance of these houses with a filling limit of 500 people will cost the state about 75 billion rubles, which is not economically profitable. The purpose of the work is to formulate proposals regarding the optimization of application and legislative regulation of arrest as a measure of criminal law influence. To achieve the stated goal, following tasks are formulated and sequentially solved in the work: to conduct a retrospective analysis of arrest as a type of criminal punishment; to reveal doctrinal views regarding the declared measure of state coercion, presented on the pages of specialized literature; to identify the essential differences between arrest and other punishments related to the isolation of the convict from society; to determine the financial and economic feasibility of building arrest houses on the territory of Russian Federation.